Case Report: Brachydactyly Type A1 Induced by a Novel Variant of in-Frame Insertion in the IHH Gene - Zeng, Feier; Liu, Huan; Xia, Xuyang; Shu, Yang; Cheng, Wei; Xu, Heng; Yin, Geng; Xie, Qibing (Frontiers in Genetics, 2022)
Brachydactyly type A1 (BDA1) is an autosomal dominant inherited disease characterized by shortness/absence of the middle phalanges, which can be induced by mutations in the Indian hedgehog gene (IHH). Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease characterized by joint destruction, synovitis and the presence of autoantibodies. In this study, the proband was diagnosed with both BDA1 and RA. We performed whole-exome sequencing in a four-generation Chinese family to investigate their inherited causal mutation to BDA1. A novel in-frame insertion variant in IHH: NM_002181.4: c.383_415dup/p.(R128_H138dup) was identified in the BDA1 pedigree. This insertion of 11 amino acids was located in the highly conserved amino-terminal signaling domain of IHH and co-segregated with the disease status. This adds one to the total number of different IHH mutations found to cause BDA1. Moreover, we found a potential causal germline variant in CRY1 for a molecular biomarker of RA (i.e., a high level of anti-cyclic citrullinated peptide). Collectively, we identified novel variants in IHH for inherited BDA1, which highlights the important role of this gene in phalange development.